Effects of two processing methods on some nutrients and antinutritional factors in yellow yam (Dioscorea cayenensis) - Akin-Idowu, P.E.; Asiedu, Robert; Maziya-Dixon, B.B.; Odunola, A.; Uwaifo, A. (2009)
Raw and processed tubers from eight genotypes of yellow yam (Dioscorea cayenensis) were evaluated for their contents of iron, zinc, calcium, phosphorus, total carotenoids, vitamin C, phytic acid and tannin. The mean values obtained (in mg/kg on dry weight basis) were 7.2 for iron, 9.2 for zinc, 169.3 for calcium, 1331.3 for phosphorus, 181.8 for phytate and 353.6 for tannin. Similarly, 6.31 µg/g of total carotenoids and 37.3 mg/kg of ascorbic acid were obtained on fresh weight basis. The genotypes differed significantly (P < 0.05) in tuber contents of zinc, calcium, phosphorus, total carotenoids and vitamin C but they were similar with respect to iron, phytate and tannin contents. Genotype TDc 95-65 had the highest levels of zinc, calcium, total carotenoids and phytate while TDc 95-294 had the highest levels of iron and phytate. Tubers of TDc 95-65, TDc, 95-294, TDc 04-168 and TDc 98-136 are good sources of iron, zinc and phosphorus. The two cooking methods had little effect on the minerals but significantly reduced the levels of total carotenoid, vitamin C, phytate and tannin contents.